Techno-Economic Analysis of a Microgrid System To Increase Electricity Access in Rural Areas. - Sunario Manalu; Charles O. P. Marpaung (International Journal of Smart Grid and Sustainable Energy Technologies, 2019)
This study analyses the technical and economic performances of a microgrid system which is used to increase the electricity access in a rural area – Hutajulu village, Parmonangan district, North Tapanuli district, Indonesia. There are two types of power distributed generator used in the microgrid system, i.e., diesel generator and solar PV, and there are 20 houses in the village to be supplied electricity by the microgrid system. The results show that the generator would operate 3.754 hours per year and would supply electricity to the houses 2,456 kWh/year during the planning horizon (25 years). The levelized cost of electricity (LCOE) of the diesel generator would be US₵10.7/kWh, and the capacity factor of the diesel generator would be 14%. The average electrical efficiency of the diesel generator is found 27.2%. In case of the solar PV installed in the microgrid system, the operating hour of the solar PV during the planning horizon would be 4,426 hours/year and supplies electricity to the houses 2,153 kWh/year. The levelized cost of electricity of the solar PV would be US₵7.92/kWh.